Stevens–Johnson Syndrome identified at the University Hospital Center of Libreville, Gabon: Four case reports - Pierre Constant N Nzoghe; Landry Missounga; Sophie Coniquet; Solange Ntsame; Rim Lakhmiri; Yahia Cherrah; Samira Serragui (International Journal of Risk & Safety in Medicine, 2026)
Background Stevens–Johnson Syndrome (SJS) is a rare and severe drug-induced cutaneous reaction. However, clinical and economic data regarding its management remain poorly documented in Gabon. Therefore, this study aimed to describe the clinical characteristics, drug causality assessment, therapeutic management, and direct medical costs of four confirmed cases of SJS managed at the Libreville University Hospital Center (CHUL). Case report Four confirmed cases of SJS related respectively to lidocaine, allopurinol, amoxicillin/clavulanic acid, and flucloxacillin were identified. Drug causality assessment, performed using the French causality assessment method, the World Health Organization (WHO) scale, and the ALDEN algorithm, indicated a probable causal relationship in all cases. SCORTEN scores ranged from 0 to 1, corresponding to an estimated mortality rate of 3.2%. Therapeutic management was based on symptomatic and supportive treatment, including Polaramine, Solumedrol, Dacryoserum, eosin solution, Fucithalmic, sodium bicarbonate, Fungizone, Dexeryl, ciprofloxacin, and Exomuc, with favorable clinical outcomes observed in all patients. The mean direct medical cost of management was estimated at 225,089 CFA francs (343.14 €), with a total cost of 860,355 CFA francs (1311.60 €) for the four cases. Conclusion SJS remains a severe dermatological emergency associated with substantial management costs despite favorable clinical outcomes. These findings highlight the importance of strengthening pharmacovigilance activities and the prevention of serious adverse drug reactions.